Long‐term upper aerodigestive sequelae as a result of infection with COVID‐19. Issue 2 (9th March 2022) - Allisan‐Arrighi, Annie E.; Rapoport, Sarah K.; Laitman, Benjamin M.; Bahethi, Rohini; Mori, Matthew; Woo, Peak; Genden, Eric; Courey, Mark; Kirke, Diana N.
Abstract: Objectives: Respiratory, voice, and swallowing difficulties after severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) may result secondary to upper airway disease from prolonged intubation or mechanisms related to the virus itself. We examined a cohort who presented with new laryngeal complaints following documented SARS‐CoV‐2 infection. We characterized their voice, airway, and/or swallowing symptoms and reviewed the clinical course of their complaints to understand how the natural history of these symptoms relates to COVID‐19 infections. Methods: Retrospective review of patients who presented to our department with upper aerodigestive complaints as sequelae of prior infection with, and management of, SARS‐CoV‐2. Results: Eighty‐one patients met the inclusion criteria. Median age was 54.23 years (±17.36). Most common presenting symptoms were dysphonia ( n = 58, 71.6%), dysphagia/odynophagia ( n = 16, 19.75%), and sore throat ( n = 9, 11.11%). Thirty‐one patients (38.27%) presented after intubation. Mean length of intubation was 16.85 days (range 1–35). Eighteen patients underwent tracheostomy and were decannulated after an average of 70.69 days (range 23–160). Patients with history of intubation were significantly more likely than nonintubated patients to be diagnosed with a granuloma (8 vs. 0, respectively, p < .01). Fifty patients (61.73%) were treated for SARS‐CoV‐2 without requiring intubation and were significantly more likely to be diagnosed with muscle tension dysphonia (19 vs. 1, p < .01) and laryngopharyngeal reflux (18 vs. 1, p < .01). Conclusion: In patients with persistent dyspnea, dysphonia, or dysphagia after recovering from SARS‐CoV‐2, early otolaryngology consultation should be considered. Accurate diagnosis and prompt management of these common underlying etiologies may improve long‐term patient outcomes. Level of evidence: 4